Bilateral Vesicoureteric Reflux may be a Rare Association in Lesch-Nyhan Syndrome: A Case Report - Rahman, Habibur; Anjum, Md Firoz; Biswas, Susmita; Huque, Syed Saimul; Begum, Afroza (Bangladesh Journal of Child Health, 2017)
Abstract not available Bangladesh J Child Health 2016; VOL 40 (1) :44-48